Detection of White Spot Syndrome Virus in Brazil using Negative Staining, Immunoelectron Microscopy and Immunocytochemistry Techniques - Hipolito,M (Sociedad Chilena de Anatomía, 2012)
In this study thirty shrimp samples from commercial marine shrimp (L. vannamei) farms of southern region of Brazil were obtained. Hepatopancreas and shell scrapings fragments collected in these animals were processed by transmission electron microscopy using negative staining (rapid preparation), immunoelectron microscopy and immunocytochemistry (immunolabelling with colloidal gold particles) techniques. On the transmission electron microscopy a great number of white spot virus particles, ovoid or bacilliform-to-ellipsoid, measured 230-290 nm in length and 80-160 nm in diameter with intra-nuclear projections were visualized by the negative staining technique in 27 (90%) out of 30 samples examined. Using immunoelectron microscopy technique, the anti-VP 664 serum agllutinated a large number of particles formed by antigen-antibody interaction. In the immunocytochemistry technique, the antigen-antibody reaction was styrongly marked by the particles of colloidal gold over the virus. Notably, this is the first report, to our knowledge, describing use of these microscopy techniques to study Brazilian L. vannamei marine shrimp samples; moreover, this methodology also appears to be a viable complementary tool for diagnosing the presence of the white spot virus within shrimp tissues. Importantly, these are the first photoelectron micrographs of the WSSV in Brazil.